SURVEY, QUESTION, READ, RECITE AND REVIEW (SQ3R) TOWARDS STUDENTS’ READING ABILITY - Nst, Rinjani Syarvila; Fadlia, Fadlia; Asra, Surya (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
This study aims to determine the effect of using Survey, Question, Read, Recite and Review (SQ3R) strategy on students’ reading comprehension skill in narrative text. This study is a pre – experimental research with one group pre – test post – test design. The population in this study were students in SMPN 8 Langsa and the sample of this study were students of class VIII consisting of 35 students, twenty male students and fifteen female students. The sample in this study was selected by using purposive sampling technique. This study used instruments in the form of reading test for pre – test and post – test. For the treatment, the SQ3R strategy was used in teaching narrative text. The data collected in this study was calculated by using SPSS version 22 with a significant value of 0.05. The result of this study revealed that the mean of pre – test was 44.29. After being given treatment, the average post – test increased significantly to 8.25 with a gain of 36.28. This means that the SQ3R strategy has a strong influence on students’ reading comprehension skill. It can be concluded that there was a significant improvement on students’ reading comprehension skill.